Penerapan Pendekatan Deep Learning Terhadap Kemampuan Literasi Dini Pada Mata Pelajaran Bahasa Indonesia Siswa Kelas 2 Sekolah Dasar - Fatin Adelya Putri; Safran Safran (Bunayya: Jurnal Pendidikan Guru Madrasah Ibtidaiyah, 2026)
This study was motivated by the low level of early literacy skills among second-grade elementary school students in Indonesian language learning, as indicated by limited reading fluency, poor comprehension of simple texts, and inadequate ability to write letters and words in accordance with standard language conventions. The purpose of this study was to determine the effect of implementing the Deep Learning approach on the early literacy skills of second-grade elementary school students. This study employed a quantitative approach using a pre-experimental research design with a One-Group Pretest–Posttest Design. The research subjects consisted of 25 second-grade students at SD IT Alhijrah 2 Deli Serdang, selected using the total sampling technique. Data were collected through tests and interviews, while data analysis was conducted using the normality test and the paired-sample t-test with the assistance of IBM SPSS Statistics. The findings revealed that the mean pretest score of 68.08 increased to 86.36 in the posttest. The results of the paired-sample t-test showed a significance value of p < 0.001 (p < 0.05), indicating that H? was rejected and H? was accepted. Therefore, it can be concluded that the implementation of the Deep Learning approach had a significant effect on the early literacy skills of second-grade elementary school students in Indonesian language learning.